Pengaruh Kualitas Pelayanan Publik terhadap Tingkat Kepuasan Masyarakat di Kantor Camat Kabila Kabupaten Bone Bolango - Meriska Idji; Yakob Noho Nani; Romy Tantu (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
PPublic services consist of various efforts undertaken by government institutions to meet the needs of the community for administrative services, information, and public goods. The quality of public services is an important factor in determining the level of public satisfaction with government performance. This study aims to determine the effect of public service quality on community satisfaction at the Kabila District Office, Bone Bolango Regency. The research employed a quantitative approach with a correlational design to analyze the relationship between service quality and public satisfaction. Data were collected from service users and analyzed using statistical techniques to measure the strength of the relationship between the variables. The findings indicate that the quality of public services has a positive and significant influence on public satisfaction in Kabila District, Bone Bolango Regency. The coefficient of determination shows that service quality contributes 61.20% to public satisfaction, while the remaining 38.80% is influenced by other factors such as service fees, accessibility, service speed, information availability, officers’ attitudes, trust, facilities, comfort, and public expectations and experiences. These results demonstrate that improving service quality can increase public satisfaction and strengthen community trust in government institutions. Therefore, continuous efforts to improve service quality are essential to achieve better public service performance.